Ayşe Erkmen & Ann Veronica Janssens - A - Erkmen, Ayşe 1949-; Janssens, Ann Veronica 1956- (MER. Paper Kunsthalle, 2015)
Ayşe Erkmen (1949, Istanbul) and Ann Veronica Janssens (1956, Folkestone) are sculptors of roughly the same generation. In both their cases, sculpture is a concept that goes far beyond the three-dimensional nature of the work of art and the spatial relationship between the work and the viewer. Ayse Erkmen's artistic practice is characterised by a marked interest in the historical and social context in which a work of art is born. She makes invisible elements and structures in the surroundings temporarily or permanently visible. Ann Veronica Janssens is engaged with the sensory experience and the moment when the body and space meet. She experiments with the intangible and employs light, colour and sound in her research into the perception of space and movement. In 2016, at the invitation of the City of Ghent, Erkmen and Janssens will each be installing a permanent sculpture on the Korenmarkt. The S.M.A.K., in a double exhibition (31 October 2015 - 14 February 2016), takes the opportunity to set the designs in the broader context ocf the two artists' oeuvres and to examine how these two relate to each other.
Title from colophon; each volume has separate title on cover. - Published on the occasion of the exhibition "Ayşe Erkmen & Ann Veronica Janssens - A", S.M.A.K. Ghent, October 31, 2015 - February 14, 2016
Keywords: Erkmen, Ayşe / Exhibitions; Janssens, Ann Veronica / 1956- / Exhibitions; Sculpture, Turkish / 21st century / Exhibitions; Sculpture, English / 21st century / Exhibitions; Ausstellungskatalog; Ausstellungskatalog -- S.M.A.K. -- 31.10.2015-14.02.2016 -- Gent